How are land managers adapting in Mediterranean areas in a transitions pathways context - Barroso, Filipe (2014)
European rural landscapes face today several changes due to market liberalization, price instability, energetic crisis, food quality and security, etc. These pressures result in changes, which might indicate that an ongoing transition process is taking place in rural areas, which could represent the emergence of a new agricultural regime characterized by a shift from the formerly dominant production goals towards a more complex, contested, variable mix of production, consumption and protection goals. Therefore, new ways of managing the land arise, no longer by the conventional farmers alone but by these, plus a multiplicity of other land managers. In order to better understand the diversity of processes going on in the mediterranean rural areas, a land managers typology anchored on the transition theory perspective is proposed. It aims to show the evidence of productivist and postproductivist or multifunctional strategies linked with transitions in place. This typology exploits the combination between the management practices in the holding and the expressed attitudes towards the holding management and the landscape role. To reach this typology, 373 questionnaires to land managers were made in South Portugal.